2023
DOI: 10.3390/brainsci13030511
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Whether Iron Sequestration within the CNS of Patients with Alzheimer’s Disease Causes a Functional Iron Deficiency That Advances Neurodegeneration

Abstract: The involvement of iron in the pathogenesis of Alzheimer’s disease (AD) may be multifaceted. Besides potentially inducing oxidative damage, the bioavailability of iron may be limited within the central nervous system, creating a functionally iron-deficient state. By comparing staining results from baseline and modified iron histochemical protocols, iron was found to be more tightly bound within cortical sections from patients with high levels of AD pathology compared to subjects with a diagnosis of something o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 126 publications
1
1
0
Order By: Relevance
“…In line with a reduced iron release, we have shown that ECs incubated with holo-Tf have reduced Fpn levels (Baringer, Palsa, et al, 2023;Simpson et al, 2015). Recently, LeVine et al found that iron deficiency, iron transport, and mitochondrial related processes were all upregulated in AD patient tissue (LeVine et al, 2023). Here, we found that Aβ CM contained significantly less iron than control CM.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with a reduced iron release, we have shown that ECs incubated with holo-Tf have reduced Fpn levels (Baringer, Palsa, et al, 2023;Simpson et al, 2015). Recently, LeVine et al found that iron deficiency, iron transport, and mitochondrial related processes were all upregulated in AD patient tissue (LeVine et al, 2023). Here, we found that Aβ CM contained significantly less iron than control CM.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Ayton et al have shown that brain iron accumulation occurs early in AD and prior to widespread Aβ or tau pathology distribution associated with later disease stages (Ayton, Portbury, et al, 2021), suggesting iron uptake dysfunction occurs independently from the vascular damage Aβ can inflict in later stages of the disease (Erickson & Banks, 2013). Anemic and iron transport processes are also upregulated in AD patient brain tissue (LeVine et al, 2023), proposing the hypothesis that the AD brain may operate in functional iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the conditioned media had an increased percentage of apo-transferrin, which stimulated endothelial cells to increase iron transport [25]. In support of this, the expression of transcripts for transferrin was upregulated in the olfactory bulb of patients with early Alzheimer's disease compared to control subjects [5]. Amyloid β was also found to increase the expression of divalent metal transporter 1 (DMT1), which is thought to mediate an increased uptake of non-transferrin-bound iron in immortalized microglia [26] (Figure 1B).…”
Section: Processes Accounting For Increased Iron Accumulationmentioning
confidence: 70%
“…In addition, as a CNS disease advances, iron from degenerating cells can become sequestered within reactive microglia [9][10][11], which accumulate ferritin [12][13][14]. Once iron becomes unavailable, cells experience a functional iron deficient state that has similarities with anemia [5]. Cells can respond to a functional deficiency of iron by taking up more iron and exporting less iron [4,6].…”
Section: Pathogenic Processes Leading To a Functional Iron Deficiencymentioning
confidence: 99%
See 1 more Smart Citation